Doo-Wop Acappella : a Story of Street Corners, Echoes, and Three-Part Harmonies. - Pitilli, Lawrence (Rowman & Littlefield Publishers, 2016)
In Doo-Wop Acappella scholar and singer Lawrence Pitilli explores doo-wop acapella groups as manifestations of urban change, mass migrations, ethnic acculturation, and changing radio and recording industries. He reveals how doo-wop groups displayed the dynamics of cultural change in the "sounds"--Sonic and linguistic-that every generation seeks to make and remake for themselves